2006
DOI: 10.1051/0004-6361:20064893
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Bulge microlensing optical depth from EROS-2

Abstract: Aims. We present a new EROS-2 measurement of the microlensing optical depth toward the Galactic Bulge. Methods. Light curves of 5.6×10 6 clump-giant stars distributed over 66 deg 2 of the Bulge were monitored during seven Bulge seasons. 120 events were found with apparent amplifications greater than 1.6 and Einstein radius crossing times in the range 5 d < t E < 400 d. This is the largest existing sample of clump-giant events and the first to include northern Galactic fields. Results. In the Galactic latitude … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
163
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(185 citation statements)
references
References 37 publications
(75 reference statements)
21
163
1
Order By: Relevance
“…To explain this discrepancy, Kiraga & Paczynski (1994) suggested that the Galactic bulge could give a substantial contribution to the optical depth and thus they included this contribution in their calculations. Theoretical estimates with these new models agree well with the more recent measurements of the optical depth, τ = 2.17 × 10 −6 (Popowski et al 2005, the MACHO group), τ = 2.55 × 10 −6 (Sumi et al 2006, the OGLE-2 group) and τ = 1.62 × 10 −6 (Hamadache et al 2006, the EROS-2 group).…”
Section: Introductionsupporting
confidence: 83%
“…To explain this discrepancy, Kiraga & Paczynski (1994) suggested that the Galactic bulge could give a substantial contribution to the optical depth and thus they included this contribution in their calculations. Theoretical estimates with these new models agree well with the more recent measurements of the optical depth, τ = 2.17 × 10 −6 (Popowski et al 2005, the MACHO group), τ = 2.55 × 10 −6 (Sumi et al 2006, the OGLE-2 group) and τ = 1.62 × 10 −6 (Hamadache et al 2006, the EROS-2 group).…”
Section: Introductionsupporting
confidence: 83%
“…Besides the Magellanic results presented here, EROS-2 has also published measurements of the optical depth toward the Galactic Bulge (Afonso et al 2003b;Hamadache et al 2006). The measured optical depth is in agreement with that measured by MACHO (Popowski et al 2005), and OGLE-2 (Sumi et al 2006) and with the predictions of Galactic models (Evans & Belokurov 2002;Bissantz & Gerhard 2002;Han & Gould 2003;Wood & Mao 2005).…”
Section: Introductionmentioning
confidence: 86%
“…(7), must be compared with the observations. For that purpose, we used data collected by several leading collaborations, in particular MACHO (Popowski et al 2005), EROS (Hamadache et al 2006), OGLE (Sumi et al 2006), and MOA (Sumi & et al 2003). These data were collected and analysed in detail in a review (Moniez 2010).…”
Section: Datamentioning
confidence: 99%